Responses to Intercultural Teaching and Learning Activities Among Indonesian EFL Students - Aulia, Muhammad; Judaya M Alanazi, Mohammed (University of Kuningan, 2024)
Since Intercultural Communicative Competence was introduced, there have been multiple studies conducted to do research on how the competence can potentially improve not only students’ knowledge and skills at using the foreign language, but also students’ attitudinal development towards the culture of the foreign language. The present study focuses on the ways of how the competence has been realized and taught at Indonesian universities with varied course names in the context of English as a Foreign Language (EFL). Via a qualitative multiple case studies, forty-two students’ responses towards activities and personal changes after attending the course were elicited through interview surveys. The iterative data analyses involved data condensation, data display, data verification and conclusion. It can be found from the data that cultural sharing with discussion and presentation has been prevalent at the classroom activities despite the debate of its effectiveness. It was quite striking that the students expressed their changes of attitudes towards other foreign cultures upon the engagement of the course. This study proposes the most-suited-contextualized teaching activities for the competence in Indonesian context and strives to enrich phenomena of intercultural teaching and learning in the typical EFL contexts. All of these to support that there is no one-fit-all contexts in promoting Intercultural Communicative Competence.